REOPENING OF PROCEEDING IN ADMINISTRATIVE DISPUTE - Вучеттић, Дејан; Миленковић, Невена (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2026)
The significance of the requirement that administrative authorities act in accordance with the law-particularly when deciding, by way of individual administrative acts, on the rights, obligations, and legally protected interests of individuals-is recognized and emphasized by the highest legal act, the Constitution of the Republic of Serbia. Article 198(2) provides that: “The legality of final individual acts deciding on rights, obligations, and legally protected interests shall be subject to judicial review in an administrative dispute, unless another form of judicial protection is prescribed in a specific case.” This constitutional provision is affirmed by the Law on Administrative Disputes (hereinafter: the LAD), which, in Article 1, defines the purposes of administrative dispute proceedings as: “judicial protection of individual rights and legal interests” and “ensuring the legality of decision-making in administrative and other individual matters prescribed by the Constitution and the law.” The aims and rationale of administrative dispute proceedings clearly follow from these provisions. From the standpoint of these objectives, the administrative dispute should be understood as a unity of the system of primary and secondary administrative-judicial protection. This implies that, if the goals are not achieved in the first-phase of primary administrative-judicial protection, then the entire "burden" of their implementation "falls on the shoulders" of secondary protection-by legal means (in administrative dispute). Within this context lies the social and legal-political relevance of legal remedies in administrative dispute proceedings.   Given that the current LAD recognizes exclusively extraordinary legal remedies - Reopening of administrative disputes proceedings and a Request for Review of a Judicial Decision - and that, for the first time since the adoption of the first post-war LAD (1952), it entirely excludes ordinary legal remedies from the system of secondary administrative-judicial protection, it is difficult - amid comprehensive reforms of public administration and those that still await administrative judiciary reform - not to raise the following questions: Are the legal remedies provided by the governing statute adequate to ensure the realization of the objectives for which they were introduced into the system of administrative-judicial protection? How effective are they in practice? Is their level of effectiveness sufficient to justify a single-instance administrative judiciary? Finally, does the protection afforded through these remedies -substantively - correspond to that required by the right to an effective legal remedy (Article 13) and the right to a fair trial (Article 6(1)), as guaranteed by the European Convention on Human Rights?
Keywords: administrative dispute; reopening of proceeding; legal remedy; an effective legal remedy; ECHR